The Semantic Web: ESWC 2013 Satellite Events ESWC 2013, Satellite Events, Montpellier, France, May 26-30, 2013, Revised Selected Papers - Cimiano, Philipp; Fernández, Miriam; Lopez, Vanessa; Schlobach, Stefan; Völker, Johanna; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-proceedings of the satellite events of the10th International Conference on the Semantic Web, ESWC 2013, held in Montpellier, France, in May 2013. The volume contains 44 papers describing the posters and demonstrations, 10 best workshop papers selected from various submissions and four papers of the AI Mashup Challenge. The papers cover various aspects on the Semantic Web.
Parl Bench: a SPARQL-bench marker for electronic publishing applications -- Real-time detection of small scale incidents -- Ontology adaptation upon updates -- Caching and prefetching strategies for SPARQL queries.
Keywords: Information storage and retrieval; Artificial intelligence; Database management; Information Storage and Retrieval; Artificial Intelligence; Database Management